RESEARCH DATA SUPPORT AT UNIVERSITY OF WISCONSIN-MADISON: A CASE STUDY - Cook, Cameron; Patiño, Jennifer (Nazarbayev University library, 2022)
This brief case study will introduce the research data sharing and compliance landscape in the United States and the ways in which the University of Wisconsin-Madison Libraries are responding to it through their local research data support services. This study provides a brief introduction to the federal policy and data sharing context in the United States, describes structure and services provided by the UW-Madison Libraries' Research Data Services, discusses the ways the libraries are facilitating compliance with data sharing requirements through supported research data repositories, and concludes with recommendations based on lessons learned from the development and on-going support of these services.
Keywords: Type of access: Open Access; EALC 2022; research data; University of Wisconsin-Madison Libraries; Research Data Services